2019
DOI: 10.26434/chemrxiv.9630623.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Growth of Al2O3 on Size-Selected Platinum Clusters by Atomic Layer Deposition

Abstract: In heterogeneous catalysis, atomic layer deposition (ALD) has been developed as a tool to stabilize and reduce carbon deposition on supported nanoparticles. Here, we discuss use of high vacuum ALD to deposit alumina films on size-selected, sub-nanometer Pt/SiO2 model catalysts. Mass-selected Pt24 clusters were deposited on oxidized Si(100), to form model Pt24/SiO2 catalysts with particles shown to be just under 1 nm, with multilayer three dimensional structure. Alternating exposures to trimethylaluminum and wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…CS depositions were performed by a laser ablation cluster source which has been used and described in several previous publications. 58,60,62 For cluster source-deposition of bare Ru 3 clusters, the source was a 99.9% pure target of Ru.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CS depositions were performed by a laser ablation cluster source which has been used and described in several previous publications. 58,60,62 For cluster source-deposition of bare Ru 3 clusters, the source was a 99.9% pure target of Ru.…”
Section: Methodsmentioning
confidence: 99%
“…CO-TPD is used to probe the available CO adsorption sites on the metal clusters, as well as for probing the removal of ligands with heating in the case of CO-stabilized clusters. 19,20,[56][57][58][59][60] XPS is used to analyse the composition of the surface and to determine concentration depth proles.…”
Section: Introductionmentioning
confidence: 99%
“…To probe this, we performed a series of 13 CO TPD experiments. CO is not just a relevant carbonaceous adsorbate, but also is a useful TPD probe that binds strongly to Pt clusters, 10,34 and reports on the number and energetics of reactant- Multiple TPD runs, each with 180 K CO exposure, were run to assess changes in the CO binding site distribution driven by the TPD process (Fig. 3a).…”
Section: Co Tpdmentioning
confidence: 99%
“…There are many ways that have been considered for sintering prevention. 3,[7][8][9][10] One way is by doping or co-alloying of precious metals with other elements to favorably modify its electronic structure. It has been suggested that, when used at a proper ratio, Pd can be used as a dopant in order to decrease Pt clusters sintering on TiO 2 (110).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation